Failing Forward: How CARE is Focusing on What Goes Wrong to Improve Impact - Janoch, Emily (CLA Case Competition, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs.

Context-monitoring for adaptive management - Pickwick, Sarah (World Vision, 2022)